Pengaruh Pedagogik, Diferensiasi, dan Pendekatan Humanistik Guru terhadap Pembelajaran PAK Berkualitas di SMTK Jakarta-Banten - Pasaribu, Novelia; Istiati, Istiati (STT Pelita Dunia, 2025)
This study is motivated by the gap between the Christian Religious Education (PAK) curriculum, which promotes active, participatory, and student-centered learning, and the prevailing classroom practices that remain largely one-way and cognitively oriented. The research aims to analyze the influence of teachers’ pedagogical competence, differentiated instruction strategies, and humanistic approaches on the quality of PAK learning in Christian Theological High Schools (SMTK). A quantitative approach was used with an explanatory survey method involving 129 respondents, consisting of students from SMTKs in Jakarta and Banten. The results of multiple linear regression analysis show that all three variables simultaneously have a significant effect on learning quality (F = 125.921; p < 0.001), with a contribution of 75.1%. Partially, the humanistic approach has the most dominant influence (59.6%), followed by pedagogical competence (25.8%), while differentiated instruction was not statistically significant. These findings highlight the importance of responsive and relational teacher professionalism in PAK.